2013
DOI: 10.1002/clen.201200142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Composts from Agricultural Wastes with Fish Pond Sediment as Bulking Agent to Improve Compost Quality

Abstract: Composts with five different ratios of agricultural wastes, viz. rice straw (RS), wheat straw (WS), potato plant (PP), and mustard stover (MS) were prepared with or without fish pond bottom sediment to investigate the compost maturity and their suitability for field application. The composting process was monitored through the changes in physico‐chemical parameters and germination index (GI) at every 7 days interval of the composting process. All the composts were dark brown and smelled like forest soil within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…Means in a column followed by the same letter are not significantly different at p 6 0.05 by LSD. a IR = ideal range, according to Zhang and Sun (2014a), Karak et al (2013), and Hue and Liu (1995). …”
Section: Sample Collection and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Means in a column followed by the same letter are not significantly different at p 6 0.05 by LSD. a IR = ideal range, according to Zhang and Sun (2014a), Karak et al (2013), and Hue and Liu (1995). …”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…This new method results in two peaks in composting temperature (at 55-60°C or even higher) and a longer thermophilic period. As a consequence, the production of a mature and stable compost requires only 30 days rather than the 90-270 days required for traditional composting (Zhang et al, 2013 Previous studies have indicated that the addition of various substances to the composting mass can accelerate the composting time and improve the quality of the compost product (Gabhane et al, 2012;Karak et al, 2013;Makan, 2015). One of these additives, sugarcane bagasse (SCB), is the fibrous residue left after the crushing and extraction of juice from sugar cane stalks during the manufacture of raw sugar (Mohee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Composting of rice straws (RS), wheat straws (WS), potato plants (PP) and mustard stovers (MS) with fish pond bottom was conducted by Karak et al [15]. This composting process was conducted for 56 days by using a heap as compost box, with the dimension of 2.5 m x 1.5 m x 1.5 m. For all of the compost preparations, the temperature of compost at the first day ranged from 24 to 26.8 C and increased to 81 C before becoming constant.…”
Section: Agriculture Wastesmentioning
confidence: 99%
“…11 Very recent study reported by . 12 concluded that HMs contaminated roadside pond sediment can increase the level of antioxidants (cysteine and ascorbic acid) in roots, shoots and leaves of Brassica juncea which makes the plant is well adapted to tolerate and accumulate high quantities of HMs. Hence the role of heavy metals on antioxidant activity in plant is an important focus which can't be overlooked.…”
Section: Introductionmentioning
confidence: 99%